Resistance of Permafrost and Modern Acinetobacter lwoffii Strains to Heavy Metals and Arsenic Revealed by Genome Analysis. (4th October 2016) - Mindlin, Sofia; Petrenko, Anatolii; Kurakov, Anton; Beletsky, Alexey; Mardanov, Andrey; Petrova, Mayya
Abstract : We performed whole-genome sequencing of five permafrost strains of Acinetobacter lwoffii (frozen for 15–3000 thousand years) and analyzed their resistance genes found in plasmids and chromosomes. Four strains contained multiple plasmids (8–12), which varied significantly in size (from 4, 135 to 287, 630 bp) and genetic structure; the fifth strain contained only two plasmids. All large plasmids and some medium-size and small plasmids contained genes encoding resistance to various heavy metals, including mercury, cobalt, zinc, cadmium, copper, chromium, and arsenic compounds. Most resistance genes found in the ancient strains of A . lwoffii had their closely related counterparts in modern clinical A . lwoffii strains that were also located on plasmids. The vast majority of the chromosomal resistance determinants did not possess complete sets of the resistance genes or contained truncated genes. Comparative analysis of various A . lwoffii and of A . baumannii strains discovered a number of differences between them: (i) chromosome sizes in A . baumannii exceeded those in A . lwoffii by about 20%; (ii) on the contrary, the number of plasmids in A . lwoffii and their total size were much higher than those in A . baumannii ; (iii) heavy metal resistance genes in the environmental A . lwoffii strains surpassed those in A . baumannii strains in the number and diversity and were predominantly located on plasmids. Possible reasons for these differences are discussed.